(3QSGdI aj eUWdM GdMOjKs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI ; heeG MQQg HYV GdeTGjN ef eUWdM GdLOjK bhdg (B: (3GdMOjK gh GSe ef GdJMOjK hgh GdENHGQ Ke Sei Hg bhd Ch aYd Ch JbQjQ fSH Edi GdfHj Udi Gddg Ydjg hSde hjLeY Ydi CMGOjK Ydi NdGa GdbjGSs
(3BNQgG (B:s
(3bGdhG hjfHZj def CQGO QhGjI MOjK Ch PcQg Cf jfXQ aEf cGf UMjMG Ch MSfG jbhd bGd QShd Gddg Udi Gddg Ydjg hSde cPG Ch aYd cPG Ch fMh Pdc ef UjZ GdLRe hEf cGf VYjaG adG ojbGd HUjZI GdLRe Hd ojbGd Qhj Yfg cPG Ch ojQhi Yfg cPG Ch LGA Yfg cPG Gh ojPcQ Ch ojMci Ch ojbGd HdZfG Ch eG THg Pdcs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdMOjK hGdeUWdMs